684 A low affinity bivalent mesothelin-binding MATCH4 multispecific T cell engager increases cytotoxic selectivity for high mesothelin expressing cells. (10th December 2020) - Chatterjee, Bithi; Simonin, Alexandre; Snell, Daniel; Gunde, Tea; Hess, Christian; Brock, Matthias; Warmuth, Stefan; Weinert, Christopher; Kirk, Niels; Diem, Dania; Flückiger, Naomi; Heiz, Robin; et al.
Abstract : Background: The effective treatment of solid tumors remains an unmet medical need. Several concepts exist to treat malignancies, including antibody-drug or -immunotoxin conjugates, immune checkpoint inhibition, CAR- T cells, as well as bispecific T cell engagers. CD3-based T cell engagers are highly potent therapeutic molecules with T cell cytotoxicity activities in the picomolar range. Alongside this highly potent anti-tumor activity is the risk of on-target off-tumor effects due to low levels of expression of the target antigen in normal tissue, as has been observed for the tumor-associated antigen mesothelin (MSLN). Methods: Low-affinity antibody fragments to the tumor-associated antigen MSLN were generated, and a multispecific MATCH4 molecule was constructed containing bivalent low-affinity MSLN binding domains, a CD3 binding domain, and a serum albumin-binding domain for half-life extension. This molecule was tested in a cytotoxicity assay using human PBMCs co-cultured with H226 or MeT-5A cells, which express high or low levels of MSLN, respectively. The MeT-5A line, derived from mesothelial cells in the pleural fluid of non-cancerous individuals, represents normal MSLN-expressing cells. Soluble MSLN was added to determine effects on cytotoxicity. In vivo xenograft mouse studies were conducted using a tumor cell/PBMC co-implantation model, followed by regular dosing with molecules of interest. Results: Here we report the design and the promising preclinical activity of the MATCH4 molecule in vitro and in vivo. We demonstrate that the low-affinity bivalent MSLN T cell engager has increased in vitro potency in T cell activation and tumor cell killing, as compared to a high-affinity monovalent counterpart on high MSLN expressing cells. We also demonstrate that the activity on low MSLN expressing cells is reduced for the low-affinity bivalent compared to the high affinity monovalent molecule. Because soluble MSLN is shed from cancer cells into cancer patient serum, we also demonstrate that up to 500 ng/mL of soluble MSLN does not interfere with the cytotoxic activity of the low affinity bivalent T cell engager, compared to the effects of soluble MSLN on a high affinity monovalent T cell engager. Importantly, we demonstrate in vivo that the low-affinity bivalent molecule significantly inhibits tumor growth in a dose-dependent manner. Conclusions: Collectively, these data demonstrate anti-tumor efficacy by this novel multispecific low affinity bivalent T cell engager. These data indicate the potential of this molecule to increase the therapeutic window by reducing safety concerns on normal tissue where MSLN expression is low, and yet increase cytotoxicity to MSLN-expressing cancer cells.